2020
DOI: 10.1177/0309324720924580
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of strain measurement systems on a non-isotropic material and its uncertainty on finite element analysis

Abstract: The application of strain gauges as recommended by the ASTM standards provides accurate strain measurements in isotropic materials. However, their use in composite materials becomes more challenging due to their anisotropic nature. In this study, we hypothesized that the use of the distributed sensing system and the three-dimensional digital image correlation, which can average strain along a line and surface, respectively, may account for strain variability in composite materials. This study shows an investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Each section was then assigned material properties using the stiffness matrix definition, which depended on the individual plies orientation relative to the global reference. The material properties used, sourced from [13], are shown in Table 1. In contrast to the approach used during the ASTM™ block study, the water path part itself was moved as a whole along the surface of the inspected region.…”
Section: Thin Composite Laminate With Embedded Defectsmentioning
confidence: 99%
“…Each section was then assigned material properties using the stiffness matrix definition, which depended on the individual plies orientation relative to the global reference. The material properties used, sourced from [13], are shown in Table 1. In contrast to the approach used during the ASTM™ block study, the water path part itself was moved as a whole along the surface of the inspected region.…”
Section: Thin Composite Laminate With Embedded Defectsmentioning
confidence: 99%
“…Investigating the local performance of the material in the area near the crack tip can explain the fracture resistance properties of this material. The amplitude of vertical strain at the crack tip and its effect on the area around the crack are two factors used to explain the crack propagation tendency [4,[35][36][37]. These two factors can be implemented utilizing the full-field displacement distribution acquired from the DIC technique [13,38].…”
Section: Investigation Of Strain Distributionmentioning
confidence: 99%
“…Martinez-Bueno et al made use of Rayleigh backscattering technology to instrument and validate a Finite Element Model (FEM) of a composite wing of an Unmanned Aerial Vehicle (UAV) [19]. In [20], Baldassarre et al demonstrated the accuracy of the FODSS with respect to discrete singlepoint measurements such as strain gauges and surface strain measurement technology such as DIC. The author concluded that for anisotropic materials, surface strain measurements such as DIC showed that they were more accurate than a single point or line measurement technique.…”
Section: Introductionmentioning
confidence: 99%